Use of satellite observed cloud patterns for the analysis of 500-mb level in tropics (MAUSAM, 1971)
This paper illustrates the use of a quasi objective scheme suggested by Nagle etal. (1970), to utilize satellite observed cloud patterns for the analysis of 500 mb height field in the areas of sparse network in the tropics.         The scheme based on, only satellite pictures, provides a very useful first guess field for the machine analysis and excellent guide, especially over areas of scanty data, for the conventional analyst.            The basic limitations of the scheme for its use over the tropice and future studies required for its best exploitation have also been briefly discussed.